Practices of Claiming Control and Independence in Couple Therapy With Narcissism - Janusz, Bernadetta; Bergmann, Jörg R.; Matusiak, Feliks; Peräkylä, Anssi (Frontiers in Psychology, 2021)
Four couple therapy first consultations involving clients with diagnosed narcissistic problems were examined. A sociologically enriched and broadened concept of narcissistic disorder was worked out based on Goffman’s micro-sociology of the self. Conversation analytic methods were used to study in detail episodes in which clients resist to answer a therapist’s question, block or dominate the development of the conversation’s topic, or conspicuously display their interactional independence. These activities are interpreted as a pattern of controlling practices that were prompted by threats that the first couple therapy consultation imposes upon the clients’ self-image. The results were discussed in the light of contemporary psychiatric discussions of narcissism; the authors suggest that beyond its conceptualization as a personality disorder, narcissism should be understood as a pattern of interactional practices.